2020
DOI: 10.3389/fcell.2020.595917
|View full text |Cite
|
Sign up to set email alerts
|

ASB7 Is a Novel Regulator of Cytoskeletal Organization During Oocyte Maturation

Abstract: Ankyrin repeat and SOCS box (ASB) family members have a C-terminal SOCS box and an N-terminal ankyrin-related sequence of variable repeats. To date, the roles of ASB family members remain largely unknown. In the present study, by employing knockdown analysis, we investigated the effects of ASB7 on mouse oocyte meiosis. We show that specific depletion of ASB7 disrupts maturational progression and meiotic apparatus. In particular, abnormal spindle, misaligned chromosomes, and loss of cortical actin cap are frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…We also used I-TASSER to search for structural homologs, but this search too yielded no results (35). Six proteins identified in our screen contained ankyrin repeat domains, scaffolds for protein recognition and interaction, which are present in actin regulators in other organisms (37,38). We also found four alpha-giardins, annexin-like cytoskeletal proteins unique to Giardia (39).…”
Section: Discussionmentioning
confidence: 99%
“…We also used I-TASSER to search for structural homologs, but this search too yielded no results (35). Six proteins identified in our screen contained ankyrin repeat domains, scaffolds for protein recognition and interaction, which are present in actin regulators in other organisms (37,38). We also found four alpha-giardins, annexin-like cytoskeletal proteins unique to Giardia (39).…”
Section: Discussionmentioning
confidence: 99%
“…We also used I-TASSER to search for structural homologs, but this search, too, yielded no results ( 35 ). Six proteins identified in our screen contain ankyrin repeat domains, scaffolds for protein recognition and interaction, which are present in actin regulators in other organisms ( 37 , 38 ). We also found four alpha-giardins, annexin-like cytoskeletal proteins unique to Giardia ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that BPF exposure was associated with a remarkable increase in acetylated α‐tubulin levels than the controls, implying that microtubule stability might be a major cause of abnormal spindle assembly. Accurate chromosome segregation during meiosis depends on the appropriate spindle assembly and formation of correct kinetochores‐microtubule interactions 38 . Aberrant spindle assembly and chromosome alignment can activate the spindle assembly checkpoint (SAC), impeding the anaphase‐promoting complex to avert anaphase until all kinetochores are correctly attached 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Accurate chromosome segregation during meiosis depends on the appropriate spindle assembly and formation of correct kinetochores-microtubule interactions. 38 Aberrant spindle assembly and chromosome alignment can activate the spindle assembly checkpoint (SAC), impeding the anaphase-promoting complex to avert anaphase until all kinetochores are correctly attached. 39 The high rate of abnormal spindle structure could be due to activated SAC at the M I stage.…”
Section: Comparison Of the Effects Of Bpf And Bpa On Dna Damage And O...mentioning
confidence: 99%